Smartphone use and its addiction among adolescents in the age group of 16-19 years - Dinesh J Bhanderi; Yogita P Pandya; Deepak B Sharma (Wolters Kluwer Medknow Publications, 2021)
Background: Smartphone use is escalating among adolescents, thereby increasing the risk of its addiction among them. Objective: The objective of this study was to estimate the prevalence of smartphone use and its addiction among adolescents in 16-19 years of age group. Materials and Methods: An observational cross-sectional study was conducted among 496 students in the age group of 16-19 years. Relevant information was collected using a self-administered questionnaire and the Smartphone Addiction (SA) Scale. Chi-square test and logistic regression were applied to study the association between independent and dependent variables. Results: Smartphone use was found to be 83.9%. It was associated with age, area of residence, discipline, use of hands-free kit, and parents' education and income. The smartphone addiction rate was reported to be 37%. It was found to be associated with age, area of residence, place of education, duration of smartphone use, daily hours of use, perception that cellphone use is harmful to health, and parents' education and income. Conclusion: A high rate of SA among adolescents warrants effective strategies at local, state, and national level to address this growing health problem in this population.